2022
DOI: 10.1088/2515-7639/ac442b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast carrier dynamics at organic donor–acceptor interfaces—a quantum-based assessment of the hopping model

Abstract: We investigate the charge transfer dynamics of photogenerated excitons at the donor-acceptor interface of an organic solar cell blend under the influence of molecular vibrations. This is examined using an effective Hamiltonian, parametrized by density functional theory calculations, to describe the full quantum behaviour of the relevant molecular orbitals, which are electronically coupled with each other and coupled to over one hundred vibrations (via Holstein coupling). This electron-phonon system is treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…For similar polymers Barszcz et al [48] identified the C-C stretching vibration of thiophene rings at ≈0.173 eV and the in-phase C=C stretching of the DPP core at ≈0.2 eV. Similar results have been presented by Adil et al [49], Francis et al [50] and Dorfner et al [51]. If we assume coupling to the phonon modes as the origin for the excited states, these results compare very well with the electrically measured results in this work, which proves that excited states can be investigated also for OSCs via charge transport measurements.…”
Section: Resultssupporting
confidence: 62%
“…For similar polymers Barszcz et al [48] identified the C-C stretching vibration of thiophene rings at ≈0.173 eV and the in-phase C=C stretching of the DPP core at ≈0.2 eV. Similar results have been presented by Adil et al [49], Francis et al [50] and Dorfner et al [51]. If we assume coupling to the phonon modes as the origin for the excited states, these results compare very well with the electrically measured results in this work, which proves that excited states can be investigated also for OSCs via charge transport measurements.…”
Section: Resultssupporting
confidence: 62%
“…In the literature, that process has been reported with a variety of time constants, both experimentally 10,22,24,25 and theoretically. 45 The CTS observed in our study forms after the transfer of one of the charges and might not be distinguishable in transient absorption spectroscopy in other spectral regions.…”
mentioning
confidence: 62%
“…† Models of this kind are common for the phenomenological description of vibrational coherent effects, electronic non-adiabatic couplings and vibrational relaxation/dephasing in various systems, [54][55][56][57] including electron transfer donor-acceptor systems 58 and organic interfaces. 59 Due to the enormous complexity and multidimensionality of the LHN system, we cannot give a microscopic underpinning or parameterization of the model Hamiltonian. The validity of this reduced description is verified a posteriori, since it gives a clear and insightful interpretation of the experimental signals.…”
Section: Theoretical Analysismentioning
confidence: 99%